Numerical investigation of temperature distribution and thermal performance while charging-discharging thermal energy in aquifer. (25th March 2017) - Ganguly, Sayantan; Mohan Kumar, M.S.; Date, Abhijit; Akbarzadeh, Aliakbar
Highlights: A 3D coupled thermo-hydrogeological numerical model of an ATES system is presented. Importance of a few parameters involved in the study is determined. Thermal energy discharge by the ATES system for two seasons is estimated. A strategy and a safe well spacing are proposed to avoid thermal interference. The proposed model is applied to simulate a real life ATES field study. Abstract: A three-dimensional (3D) coupled thermo-hydrogeological numerical model for a confined aquifer thermal energy storage (ATES) system underlain and overlain by rock media has been presented in this paper. The ATES system operates in cyclic mode. The model takes into account heat transport processes of advection, conduction and heat loss to confining rock media. The model also includes regional groundwater flow in the aquifer in the longitudinal and lateral directions, geothermal gradient and anisotropy in the aquifer. Results show that thermal injection into the aquifer results in the generation of a thermal-front which grows in size with time. The thermal interference caused by the premature thermal-breakthrough when the thermal-front reaches the production well results in the fall of system performance and hence should be avoided. This study models the transient temperature distribution in the aquifer for different flow and geological conditions which may be effectively used in designing an efficient ATES project by ensuring safety from thermal-breakthrough while catering to the energy demand. Parameter studies are also performed which reveals that permeability of the confining rocks; well spacing and injection temperature are important parameters which influence transient heat transport in the subsurface porous media. Based on the simulations here a safe well spacing is proposed. The thermal energy produced by the system in two seasons is estimated for four different cases and strategy to avoid the premature thermal-breakthrough in critical cases is also discussed. The present numerical model results are validated using an analytical model and also compared with results from an experimental field study performed at an ATES test site at Auburn University. The present model results agree with the analytical model very well and have been found to approximate the field results quite well.